Trends, levels, and projections of Head and Neck Cancer in China between 2000 and 2021: Findings from the Global Burden of Disease 2021 - Meng Wu; Hao Chen; Wei Zhang; Xingyu Feng; Shuangyue Zhang (PLoS ONE, 2025)
Head and neck cancer (HNC), a condition that is both disfiguring and potentially fatal, has become a critical public health challenge. This study seeks to evaluate the trends in HNC burden and predict its future trajectory in China. Utilizing data from the 2021 Global Burden of Disease database, we focused on the incidence, mortality, and disability-adjusted life years related to lip and oral cavity, nasopharyngeal, and laryngeal cancers within the country. We analyzed changes in incidence and mortality rates using the estimated annual percentage change, age-period-cohort (APC) analysis, and decomposition analysis. Additionally, an Autoregressive Integrated Moving Average model was employed to forecast the future burden of HNC. In 2021, China’s incidence rates for lip and oral cavity, nasopharyngeal, and laryngeal cancers were higher than those in 40.98%, 98.05%, and 50.73% of countries worldwide, respectively. The burden of HNC increases significantly with age, particularly among men. The APC analysis indicates a rising incidence of HNC among younger adults. Decomposition analysis comparing 2021–2019 highlighted that ASIR and aging were the primary factors influencing the number of cases and deaths. Projections indicate that the burden of HNC in China is expected to continue rising. To combat this growing issue, it is imperative to enhance public health strategies that focus on prevention, early detection, and efficient resource allocation.